Determinants of the Voluntary Formation of a Company Audit Committee: Evidence from Palestine - Yousef M. Hassan; Rafiq H. Hijazi (Asian Academy of Management Journal of Accounting and Finance, 2015)
Drawing on agency theory, this paper investigates the determinants of voluntary audit committee (AC) formation among non-bank firms listed on the Palestine Stock Exchange (PSE). We used the annual reports of nearly all non-bank companies listed on the PSE as well as the company guides issued by the PSE for the period between 2010 and 2012. Logistic regression analysis was performed to identify the influence of a set of corporate governance mechanisms, ownership structures and company characteristics on the voluntary formation of ACs among non-bank Palestinian firms. The result of the analysis demonstrated that the AC is influenced by foreign ownership, institutional ownership, board diligence and external auditor type. This paper adds to the limited AC literature in Middle Eastern countries in general and in the Arab World in particular. This paper not only examines the determinants of the voluntary formation of ACs but also attempts to theorise about this formation.